Does offending intensify as exposure to violence aggregates? Reconsidering the effects of repeat victimization, types of exposure to violence, and poly-victimization on property crime, violent offending, and substance use. (November 2017) - Farrell, Chelsea; Zimmerman, Gregory M.
Abstract: Purpose: The relationship between exposure to violence and adverse behavioral outcomes is well-documented. But, heterogeneity in this relationship across different operational strategies for exposure to violence is less well understood. This study examines the effects of repeat victimization, exposure to different types of violence, and poly-victimization on property crime, violent offending, and substance use. Methods: We analyze two waves of data from the National Longitudinal Study of Adolescent to Adult Health ( N  = 12, 603). We operationalize exposure to violence as: a dichotomous indicator of overall occurrence; exposure to multiple incidents of violence (repeat exposure); types of exposure to violence (witnessed, threatened, and experienced violence); and poly-victimization (i.e., repeat exposure to violence and exposure to multiple types of violence). Results: Exposure to violence – regardless of how it is measured – increases offending risk. The strongest effects are observed for poly-victimization, followed by repeat exposure to violence and exposure to a single episode of violence. There is little variation in effect sizes across types of exposure to violence. Conclusions: The results speak to the utility of preventing the onset of exposure to violence and addressing ongoing exposure to violence in order to interrupt the link between exposure to violence and offending. Highlights: Exposure to violence, regardless of how it was measured, increased offending risk. Poly-victimization had the strongest effects on offending. Repeat exposure to violence was a robust predictor of offending. There was little variation in effect sizes across types of exposure to violence.